Procurement principles and management in the digital age - Baily, Peter J. H.; Farmer, David H.; Crocker, Barry; Jessop, David (Harlow, England ; New York : Pearson, 2022)
"The twelfth edition has been substantially updated with many additi ons in the form of more detailed case studies, additional academic cont ent and the inclusion of more practical examples of best practice in ma ny key areas. Some of them are: the inclusion of three self-assessment tasks at the end of each chapter; a comprehensive review of the future of procurement; material explaining the long-term changes in strategy i n response to supply disruptions caused by disasters and by the Covid p andemic inserted into various chapters; a revised chapter considering I ndustry 4.0 tools such as e-procurement, Blockchain, the Internet of Th ings, Big Data, artificial intelligence (AI), bots, digitalisation and analytics; diversity and supplier diversity considered in detail; the i nclusion of supply chain resilience approaches; considerable coverage of sustainability provided across relevant chapters; the inclusion of s ocial value strategies and approaches; the inclusion of virtual negotia tion approaches in response to the growing trend of working from home; in the wake of the Covid pandemic, updated additional material explorin g offshoring/onshoring; third sector/not-for-profit procurement conside red; additional material for coverage of risk; consideration of just-in -case inventory as a method of improving resilience; the inclusion of t he procurement of consultancy; the inclusion of a Contract Management C ycle; retail procurement completely revised to include omnichannel cha llenges and digital tools; supplier relationship management (SRM) expa nded to include two-way, 360-degree relationship measurement; the addi tion of quality function deployment (QFD) and the House of Quality (HOQ ); ratio analysis for analysing financial viability of suppliers now i ncluded"--
Includes index.
Keywords: Purchasing -- Management; Industrial procurement -- Management